Static Subjective Visual Vertical (SVV) in Patients with Vestibular Migraine - Bogle, Jamie M.; King, Ashley Zaleski; Deep, Nicholas; Weisskopf, Peter; Starling, Amaal J. (Journal of the American Academy of Audiology, 2022)
Background Vestibular migraine (VM) is one of the common causes of episodic dizziness, but it is underdiagnosed and poorly understood. Previous research suggests that otolith reflex pathway performance is often impaired in this patient group, leading to altered perception of roll plane stimuli. Clinically, this perception can be measured with subjective visual vertical (SVV) testing.Purpose The aim of this study is to compare static SVV performance (absolute mean SVV tilt, variance) in a cohort of patients diagnosed with VM to results obtained from clinically derived normative data.Study Design Retrospective case review.Study Sample Ninety-four consecutive patients between 18 and 65 years of age diagnosed with VM were included in this comparison to clinically derived normative data.Data Collection and Analysis Retrospective chart review was completed. Demographic data, symptom report, and vestibular laboratory results were documented. SVV performance was documented in terms of absolute mean SVV tilt and response variance.Results Abnormal mean SVV tilt was described in 54% (n = 51) of patients with VM. Including abnormal response variance increased those identified with abnormal presentation to 67% (n = 63). Laboratory findings were insignificant for semicircular canal function, but of those with abnormal ocular vestibular myogenic potential results (n = 30), 77% (n = 23) demonstrated both abnormal SVV and utriculo-ocular reflex performance. There were no associations noted for SVV performance and demographic or other self-report variables.Conclusion Absolute mean SVV tilt and response variance are often abnormal in patients diagnosed with VM. These findings support theories suggesting atypical intralabyrinthine integration within the vestibular nuclei and cerebellar nodular pathways.
Keywords: vestibular; migraine; otolith; vertical